2004
DOI: 10.1038/sj.bmt.1704682
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir for treating adenoviral hemorrhagic cystitis in hematopoietic stem cell transplant recipients

Abstract: Cross ResistanceCidofovir-resistant isolates selected in vitro following exposure to increasing concentrations of cidofovir were assessed for susceptibility to ganciclovir and foscarnet 4 . All were cross resistant to ganciclovir, but remained susceptible to foscarnet. Ganciclovir-or ganciclovir/foscarnet-resistant isolates that are cross resistant to cidofovir have been obtained from drug naive patients and from patients following ganciclovir or ganciclovir/ foscarnet therapy. To date, the majority of gancicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 25 publications
2
80
1
Order By: Relevance
“…2,13 Encouraging results with antiviral agents have been published; however, there is no evident proof in a large number of patients and mainly improve clinical symptoms. [14][15][16][17] The use of formalin, alum, prostaglandin E1, estrogens, FVIIa, factor XIII, hyperbaric oxygen treatment, intravesicular sodium hyaluronate, recombinant human epidermal growth factor or recombinant human GM-CSF has been described, but their efficacy remains controversial. [18][19][20][21][22][23][24][25][26][27] Severe HC may also require surgical treatment with cystoscopy and cauterization, and even cystectomy when previous methods have failed, 28 but it is limited by the disadvantage of operation.…”
Section: Introductionmentioning
confidence: 99%
“…2,13 Encouraging results with antiviral agents have been published; however, there is no evident proof in a large number of patients and mainly improve clinical symptoms. [14][15][16][17] The use of formalin, alum, prostaglandin E1, estrogens, FVIIa, factor XIII, hyperbaric oxygen treatment, intravesicular sodium hyaluronate, recombinant human epidermal growth factor or recombinant human GM-CSF has been described, but their efficacy remains controversial. [18][19][20][21][22][23][24][25][26][27] Severe HC may also require surgical treatment with cystoscopy and cauterization, and even cystectomy when previous methods have failed, 28 but it is limited by the disadvantage of operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of this antiviral agent against HC needs to be further investigated. 23,24 Hyperbaric oxygen therapy has been shown to be effective for HC due to chemotherapy and/ or radiation therapy, and two cases of life-threatening late-onset HC after allogeneic BMT in children, which resolved after treatment with hyperbaric oxygen have been reported. 25 Surgical interventions such as cystectomy, nephrostomy, ureterostomy are associated with high rates of morbidity and mortality and are indicated for life- 27,28 Sodium hyaluronate (a member of glycosaminoglycans), is a major component of the extracellular matrix of most tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In adenovirus-induced hemorrhagic cystitis cases before acute renal failure, the most rapid and handy qualitative diagnosis kit is immunochromatography, for example, adenocheck (Santen, Osaka, Japan, or SA Scientific, Texas, U.S.) (Nagafuji et al, 2004). This kit enables us to detect more than 1x10 4 viral particles /ml in urine at the bedside, although it was developed for the diagnosis of adenovirus conjunctivitis.…”
Section: Methods Of Molecular Diagnosis For Acute Renal Failure Inducmentioning
confidence: 99%
“…Recent reports showed that 69-98% of patients with adenovirus disease were successfully treated with Cidofovir (Yusuf et al, 2006, Ljungman, 2003. Nagafuji et al reported that 71% of patients with adenovirusinduced hemorrhagic cystitis were successfully treated with Cidofovir (Nagafuji et al, 2004). Therefore, Cidofovir is recommended as the first line treatment for adenovirus-induced hemorrhagic cystitis.…”
Section: Treatment To Avoid Hemodialysis Before and During Hemorrhagimentioning
confidence: 99%
See 1 more Smart Citation